2019
DOI: 10.1177/0748806819827408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Associated With Malpractice Litigation in Rhinoplasty

Abstract: Rhinoplasty, the third most common cosmetic surgical procedure in the United States, represents the second most litigated facial plastic surgery procedure. Previous examinations of litigation specific to rhinoplasty are limited. The objective of this study was to comprehensively evaluate rhinoplasty malpractice litigation over the past 30 years and to investigate the financial burden of medical malpractice litigation associated with rhinoplasty, as well as factors that contribute to litigation and negative def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In contrast, American studies have observed that the use of supplementary, written, audiovisual, and other materials increase satisfaction after the procedure and may limit litigation 19,20 . In another study, 75% of the plastic surgeons interviewed were defendants in at least one malpractice lawsuit, and most of the investigated cases involved complaints of unsatisfactory results, excessive scarring, or lack of ICT 20 .…”
mentioning
confidence: 94%
“…In contrast, American studies have observed that the use of supplementary, written, audiovisual, and other materials increase satisfaction after the procedure and may limit litigation 19,20 . In another study, 75% of the plastic surgeons interviewed were defendants in at least one malpractice lawsuit, and most of the investigated cases involved complaints of unsatisfactory results, excessive scarring, or lack of ICT 20 .…”
mentioning
confidence: 94%